Estandarización de la citología vaginal exfoliativa correlacionando los niveles séricos de progesterona en perras durante la peri-ovulación. - Arcila Quiceno, Victor Hernan; Serrano Novoa, Cesar Augusto; Hernandez, Milena; Meza, Luz Piedad (Spei Domus, 2005)
Because accuracy of cytology as definitive test to determine the period of ovulation in canine females (dogs) it is controversial, it makes necessary to correlate typical characteristics of ovulation, as plasmatic levels of progesterone and cytogical changes to ensure optimus time of ovulation. Progesterone levels measures were carried out by ELISA test, to conclude if superficial cells percent found in vaginal cytology, is related with the hormonal levels during ovulation. Cytologic and serum samples of 30 healthy female dogs were collected every 48 hours. The datas were analysed by correlation test. When progesterone levels were below 10 ng/ml, the percentage of superficial cells was 72 +/- 1,72%, while the percentage of in flake, queratinizadas, intermediate cellular types were 13 +/- 3,12%, 84 +/- 1,14% and 16 +/- 2,62% respectively. When progestrone levels were between 10 to 20 ng/ml, the percentages of superficial cells was 68 +/- 2,08%, while in flake, queratinizadas, and intermediate cellular types were 11 +/- 3,19%, 80 +/- 1,9% and 21 +/- 3,63% respectively. Finally, within highest ranges (>20 ng/ml), the percentages of superficial cells was 57 +/- 3,52%, while in flake, queratinizadas and intermediate cells were 10 +/- 1,35%, 64+/- 2,75% and 35 +/- 3,31% respectively.